2022
DOI: 10.3897/jhr.90.79930
|View full text |Cite
|
Sign up to set email alerts
|

First report on pollinating behavior of the small carpenter bee Ceratina ridleyi Cockerell (Hymenoptera, Apidae) in Globba leucantha var. bicolor Holttum (Zingiberaceae)

Abstract: Small carpenter bees of the genus Ceratina are widespread, but little-studied as pollinators despite their presence in various pollinator assemblages. This study documents the importance of Ceratina ridleyi as a pollinator of the small-flowered Malaysian ginger Globba leucantha var. bicolor. Species of Zingiberaceae are defined by peculiar floral morphologies (e.g staminodes and a single functional anther) but are rarely studied for their insect pollinators. Surprisingly, C. ridleyi was revealed as the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Se tienen registros como polinizadores en Echium plantagineum Jacq., Medicago sativa L., y Globba leucantha var. bicolor Holttum (Ornosa y Martinez 1996, Arumugam et al 2022).…”
Section: Resultados Y Discusiónunclassified
“…Se tienen registros como polinizadores en Echium plantagineum Jacq., Medicago sativa L., y Globba leucantha var. bicolor Holttum (Ornosa y Martinez 1996, Arumugam et al 2022).…”
Section: Resultados Y Discusiónunclassified
“…For family Zingiberaceae specifically, there are estimation of 200 ginger species belong to 19 genera have been recorded in Peninsular Malaysia [8]. Recent studies indicated that gingers are commonly found in Peninsular Malaysia [9][10][11][12][13][14][15][16]. Up to date, the discovery of great number of new species and genera have been done in both lowland and highland areas of Malaysia proven by extensive research [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%